An International Review of Disciplinary Measures in Geoscience—Both Procedures and Actions - Bonham, Oliver; Abbot, David; Waltho, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
As professional communities around the world, geoscientists have in place disciplinary measures and, over time, instances have occurred which have required disciplinary actions to be taken against individuals. Geoscientists have specialized knowledge and provide expertise on which others rely for important decision-making. Geoscientists are best positioned to judge the scientific/technical and ethical merits of the work of other geoscientists. They are considered professionals and for that reason, society has placed the onus on the profession to govern itself. Consequently, it is important that appropriate disciplinary procedures are in place, that they are ever improving, and that the profession can and does act decisively when necessary.This two-part review paper examines systems and measures to uphold the ethical conduct of geoscientists (Part 1), and studies actions taken against geoscientists in the last three decades (Part 2). It uses available information collected from the member organizations of the International Union of Geological Sciences' Task Group on Global Geoscience Professionalism as well as public sources.Models used for the governance and self-regulation of geoscience practice vary globally across the same spectrum that is typical in other professions, with the choice of model varying to suit local legal contexts and societal needs and norms. Broadly, similar processes for complaints, investigation, and disciplinary decision-making (and appeals of decisions) are used. The types of charges that can be made for offences or allegations are similar. The ranges of applicable penalties vary depending on the extent of statutory power in place, but beyond this constraint, there are many parallels.Ninety-two documented cases are identified where action has been taken against geoscientists globally since 1989. Of these, 40 relate to either non-payment of dues or fees (usually discontinuation of a membership or licence) or to non-compliance with Continuing Professional Development requirements. The remaining 52 are actions for more serious offences, resulting in penalties that are more substantial. These offences cluster into six categories: 1) falsifying data; 2) fraudulent billing and/or falsifying time sheets; 3) inappropriate behaviour towards others; 4) problematic geoscience work and/or technical deficiencies; 5) misrepresentation of findings, or the giving of unsupported opinions; and 6) mixed other offences. The most frequently used penalty in these cases is the reprimand. Next most frequent is revocation. Revocations include resignations with prejudice, where the geoscientist chose to resign their membership rather than allow the matter to proceed to discipline. Suspensions, requirements for remedial education and/or fines are also frequent penalties. Combinations of different penalties are common.It is evident that rigorous procedures are in place in a number of countries and that they are being used to address the unprofessional behaviour of geoscientists. Transparency and the sharing of information about disciplinary actions between geoscience professional organizations (of all types) is important and should be encouraged. A global repository of geoscience disciplinary actions should be established and kept as up to date as possible.